Structural variability of CG-rich DNA 18-mers accommodating double T–T mismatches - Kolenko, Petr (Acta Crystallogr D Struct Biol, 2020)
Solution and crystal data are reported for DNA 18-mers with sequences related to those of bacterial noncoding single-stranded DNA segments called repetitive extragenic palindromes (REPs). Solution CD and melting data showed that the CG-rich, near-palindromic REPs from various bacterial species exhibit dynamic temperature-dependent and concentration-dependent equilibria, including architectures compatible with not only hairpins, which are expected to be biologically relevant, but also antiparallel duplexes and bimolecular tetraplexes. Three 18-mer oligonucleotides named Hpar-18 (PDB entry 6rou), Chom-18 (PDB entry 6ros) and its brominated variant Chom-18Br (PDB entry 6ror) crystallized as isomorphic right-handed A-like duplexes. The low-resolution crystal structures were solved with the help of experimental phases for Chom-18Br. The center of the duplexes is formed by two successive T–T noncanonical base pairs (mismatches). They do not deform the double-helical geometry. The presence of T–T mismatches prompted an analysis of the geometries of these and other noncanonical pairs in other DNA crystals in terms of their fit to the experimental electron densities (RSCC) and their geometric fit to the NtC (dinucleotide conformational) classes (https://dnatco.datmos.org/). Throughout this work, knowledge of the NtC classes was used to refine and validate the crystal structures, and to analyze the mismatches.